Assessment of liver and cardiac iron overload using MRI in patients with chronic anemias in Latin American countries: results from ASIMILA study. Issue 9 (21st October 2018) - Cancado, Rodolfo; Watman, Nora P.; Lobo, Clarisse; Chona, Zulay; Manzur, Fernando; Traina, Fabiola; Park, Miriam; Drelichman, Guillermo; Zarate, Juan Pablo; Marfil, Luis
ABSTRACT: Objectives: A multicenter, noninterventional, observational study was conducted in the Latin American countries including Argentina, Brazil, Colombia, Mexico, and Venezuela to assess the prevalence of liver and cardiac iron overload using magnetic resonance imaging (MRI) in patients with chronic anemias except thalassemia. Methods: Patients aged >10 years with transfusion-dependent anemias, except thalassemia, either with <20 units of red blood cell (RBC) transfusions with serum ferritin (SF) levels >2000 ng/mL or with ≥20 units of RBC transfusions regardless of SF level in their lifetime, were enrolled. Iron overload was assessed using MRI. Results: Among 175 patients included, the majority had sickle cell disease (SCD; 52%), followed by aplastic anemia (AA; 17.7%), myelodysplastic syndrome (MDS; 8.6%), Diamond-Blackfan anemia (DBA; 4%), pure red cell aplasia (1.1%), and others (16.6%). Liver iron overload was observed in 76.4% of patients, while cardiac iron overload was seen in 19.2% when assessed by MRI. The prevalence of iron overload was 80.2% in patients with SCD, 73.3% in MDS, 77.4% in AA, 100% in pure red cell aplasia, 71.4% in DBA, and 68.9% in other transfusion-related disorders. A moderate correlation between liver iron concentration (LIC) and SF was observed in patients with SCD and MDS ( r  = 0.47 and r  = 0.61, respectively). All adverse events reported were consistent with the published data for deferasirox or underlying disease. Conclusion: A high prevalence of iron overload in this patient population in Latin American countries indicates that a better diagnosis and management of iron overload is required in these countries.